Addressing Depletion in Alluvial Aquifers - Partik Kumar; Veena Srinivasan (Ecology, Economy and Society – The INSEE Journal)
India has one of the highest rates of groundwater extraction in the world, with depletion rates increasingly becoming a concern. The vast alluvial aquifers of the Indo-Gangetic Plain are vital for the country’s food security and livelihoods of millions. However, abstraction far exceeds natural recharge, resulting in a gradual decline. The hard-rock aquifers of peninsular India are also subjected to over-exploitation. But in these low-storage aquifers, it manifests as seasonal emptying and filling. In recent years, policy attention has shifted from supply-side approaches such as watershed management to demand-side measures such as participatory groundwater management under Atal Bhujal Yojana. However, the current strategies do not account for differences in geology. We argue that the management processes that worked in peninsular Indian hard-rock systems may not be suitable for alluvial aquifers, so a different approach is needed. To make this case, we draw on Ostrom’s Institutional Analysis and Development framework for the management of common-pool resources. We argue that the characteristics of groundwater resources, the socioeconomic attributes of uses and users, and the rules governing use framed by existing institutions and agrarian policies are the distinguishing features to be considered in building solutions for alluvial aquifers.